The Sense of Agency Scale: A Measure of Consciously Perceived Control over One's Mind, Body, and the Immediate Environment - Tapal, Adam; Oren, Ela; Dar, Reuven; Eitam, Baruch (Frontiers in Psychology, 2017)
The sense of agency (SoA) is defined as ‘the registration that I am the initiator of my actions’. Both ‘direct’ and ‘indirect’ measurement of SoA has focused on specific contextualized perceptual events, however it has also been demonstrated that ‘higher level’ cognitions seemingly affect the SoA. We designed a measure of person’s general, context-free beliefs about having core agency – the Sense of Agency Scale (SoAS). An EFA and CFA on samples of 236 (Study 1) and 408 (Study 2) participants yielded two correlated factors we labeled Sense of Positive Agency (SoPA) and Sense of Negative Agency (SoNA). The construct validity of SoAS is demonstrated by its low-to-moderate correlations with conceptually relevant tools and by the moderate-strong relationship between the SoNA subscale and obsessive-compulsive (OC) symptoms (r = .35). We conclude that the SoAS seems to isolate people’s general beliefs in their agency from their perceived success in obtaining outcomes.